The Influence of Islamic Financial Literacy and Risk Perception on the Financial Management Behavior of Student E-Wallet Users with Self-Control as a Mediating Variable - Fajar Budiyanto; Budi Eko Soetjipto; Madziatul Churiyah (JURNAL ECONOMINA, 2026)
This study aims to analyze the effect of Islamic financial literacy and risk perception on students’ financial management behavior in using e-wallets, with self-control as a mediating variable. This research employs a quantitative approach using a survey method involving 145 students. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that Islamic financial literacy and self-control have a significant effect on financial management behavior, while risk perception does not have a direct effect. However, risk perception significantly influences self-control. Furthermore, self-control partially mediates the relationship between Islamic financial literacy and financial behavior, and fully mediates the relationship between risk perception and financial behavior. These findings suggest that students’ financial behavior in the digital context is not solely influenced by cognitive factors but is also strongly determined by self-control in managing the ease of e-wallet transactions. This study implies that improving financial literacy must be accompanied by strengthening self-control to promote more rational and sustainable financial management behavior in the digital era.